Determinação das características do solo visando o aproveitamento geotérmico como fonte renovável de energia - Longo, Adriano José (2019)
Knowledge of the soil thermal characteristics is indispensable for dimensioning geothermal exchangers for air conditioning or yet to decrease their electric consumption. The present thesis evaluates the geothermal potential of generic soils by determining some thermal characteristics through a practical methodology, control automation and data acquisition resources in order to provide subsidies to establish the dimensions and capacity required of the heat exchangers to allow them a continuous operation. In order to evaluate the efficiency of the proposed methodology was installed in the experimental area of the Center of Excellence in Energy and Power Systems (CEESP), at the UFSM Campus in Santa Maria - RS, a set of heat exchangers placed underground in different depths. For the acquisition of data, two probes were specially developed with digital temperature sensors to be installed underground. The first 0.5 meter probe was used to measure the most superficial temperatures occurring in the soil to detect the daily temperature variations. The probe consists of 5 temperature sensors to perform measurements at 0.1 m intervals. The second probe monitored the temperature variations in the soil up to the depth of 5 meters, being composed of 11 sensors arranged 0.5 in 0.5 meters from the surface. Experiments were also conducted with a heat exchanger installed 5 meters deep, using a microcontrolled hydraulic pump, water flow and temperature sensors. The results showed that the values of thermal diffusivity found in the analysis of annual cycles are consistent with those found in the annual cycles, differentiated by the moisture content in the vertical profile.